Road to World Tourism Day 2022: Membangun Kesadaran Pariwisata Berkelanjutan melalui Edukasi Partisipatif di Kampung Sauwandarek, Raja Ampat - shidqi, Khairu Farras Shidqi; Hermawan, Hary (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2025)
Road to World Tourism Day 2022: Fostering Sustainable Tourism Awareness through Participatory Education in Sauwandarek Village, Raja Ampat. This community service activity aims to foster awareness of tourism and strengthen the values of Sapta Pesona among the residents of Kampung Wisata Sauwandarek, Meos Mansar District, Raja Ampat Regency. Conducted as part of the